A wide diversity of bacteria from the human gut produces and degrades biogenic amines. (1st January 2017) - Pugin, Benoit; Barcik, Weronika; Westermann, Patrick; Heider, Anja; Wawrzyniak, Marcin; Hellings, Peter; Akdis, Cezmi A.; O'Mahony, Liam
ABSTRACT: Background : Biogenic amines (BAs) are metabolites produced by the decarboxylation of amino acids with significant physiological functions in eukaryotic and prokaryotic cells. BAs can be produced by bacteria in fermented foods, but little is known concerning the potential for microbes within the human gut microbiota to produce or degrade BAs. Objective : To isolate and identify BA-producing and BA-degrading microbes from the human gastrointestinal tract. Design : Fecal samples from human volunteers were screened on multiple growth media, under multiple growth conditions. Bacterial species were identified using 16S rRNA sequencing and BA production or degradation was assessed using ultra-performance liquid chromatography. Results : In total, 74 BA-producing or BA-degrading strains were isolated from the human gut. These isolates belong to the genera Bifidobacterium, Clostridium, Enterococcus, Lactobacillus, Pediococcus, Streptococcus, Enterobacter, Escherichia, Klebsiella, Morganella and Proteus . While differences in production or degradation of specific BAs were observed at the strain level, our results suggest that these metabolic activities are widely spread across different taxa present within the human gut microbiota. Conclusions : The isolation and identification of microbes from the human gut with BA-producing and BA-degrading metabolic activity is an important first step in developing a better understanding of how these metabolites influence health and disease.